Strengthening the Capacity of Customary Village Leaders in Local Values Based Tourism Governance: A Community Service Program in Darmasaba Village, Badung Regency, Bali, Indonesia - Anak Agung Putu Sugiantiningsih; Rhesa Anggara Utama; Diah Rukmawati (Abdi Masyarakat, 2026)
The development of local values based rural tourism requires strong customary institutions to ensure that tourism development not only promotes economic growth but also preserves social sustainability, cultural heritage, and community harmony. Darmasaba Village, Badung Regency, Bali, possesses considerable socio cultural potential and a well-established customary village institution. However, the customary village leaders (Prajuru Desa Adat) continue to face challenges in implementing participatory, well-planned, and local values-based tourism governance. This community service program aimed to strengthen the capacity of customary village leaders in understanding, designing, and implementing local values-based tourism governance while promoting the integration of customary values into the management of the village's tourism potential. The program was implemented through a series of activities, including socialization, capacity building workshops, the introduction of appropriate technology, mentoring, evaluation, and the development of a sustainability plan. The results demonstrated significant improvements in the participants' understanding of the strategic role of customary institutions, enhanced capacity in tourism governance and organizational management, increased utilization of simple digital media for tourism promotion, and the formulation of guiding principles for local values-based tourism governance. The program also contributed to strengthening institutional capacity, fostering collaborative governance, and encouraging sustainable tourism management. In conclusion, strengthening the capacity of customary village leaders represents a strategic approach to promoting sustainable tourism governance rooted in local wisdom, reinforcing customary institutions, and improving the welfare of the Darmasaba Village community.